If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(z + 5) + -2 = 16 Reorder the terms: 3(5 + z) + -2 = 16 (5 * 3 + z * 3) + -2 = 16 (15 + 3z) + -2 = 16 Reorder the terms: 15 + -2 + 3z = 16 Combine like terms: 15 + -2 = 13 13 + 3z = 16 Solving 13 + 3z = 16 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 3z = 16 + -13 Combine like terms: 13 + -13 = 0 0 + 3z = 16 + -13 3z = 16 + -13 Combine like terms: 16 + -13 = 3 3z = 3 Divide each side by '3'. z = 1 Simplifying z = 1
| 5x+14-2=9-(4x+2) | | 60+.40x=80+.30x | | 8y-12=15y-4y | | (5n+4)(n-2)=0 | | -6(-7-5)=37+7(5) | | 2(x+9)-6=4x-8 | | x+2x+3x=480 | | 4-h=8 | | 150x+8y=275 | | -68=-2m | | 81/4+7 | | 6x-1=6x-8 | | -1/4(x+8)+1/2(x+2)=x+10 | | 2x+15-8=75 | | 8/4+7 | | 2(4x+32+8x)=16x | | -6(x-1)-5(2x-2)=64 | | 10x-3y=-30 | | 40=53+x/-5 | | -6(x-5)=-7(x+8)+x | | 3(x+2)-2=x | | e^8x+6-e=0 | | 8(p)-24=-4+-12(p) | | 4[3q-2]=16q | | 24=g/(-3) | | .24(6)+.04x=.08(12+x) | | 14-(x+3)=20 | | -7h+3h-4h-3= | | 7b-(6+b)=-22 | | 9d+8-5d-3= | | 3x/4-1/2=5/3 | | (9x+8)+12=(8x+8)+10 |